2021
DOI: 10.1145/3427955
|View full text |Cite
|
Sign up to set email alerts
|

Strategy Logic with Imperfect Information

Abstract: We introduce an extension of Strategy Logic for the imperfect-information setting, called SL ii and study its model-checking problem. As this logic naturally captures multi-player games with imperfect information, this problem is undecidable; but we introduce a syntactical class of “hierarchical instances” for which, intuitively, as one goes down the syntactic tree of the formula, strategy quantifications are concerned with finer observations of the model, and we prove that model-checki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 74 publications
0
42
0
Order By: Relevance
“…We suspect that, unlike for synchronous systems, allowing for nondeterministic choices in strategies might make a difference in the semantics. We also plan to extend our method to a larger subset of ATL * specifications, a subset of Strategy Logic (Berthon et al, 2017a), and to sATL * with epistemic operators using possibly techniques reported by Cermák et al (2014). Further experimental evaluation of the reductions on randomly generated models is also on the list.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that, unlike for synchronous systems, allowing for nondeterministic choices in strategies might make a difference in the semantics. We also plan to extend our method to a larger subset of ATL * specifications, a subset of Strategy Logic (Berthon et al, 2017a), and to sATL * with epistemic operators using possibly techniques reported by Cermák et al (2014). Further experimental evaluation of the reductions on randomly generated models is also on the list.…”
Section: Discussionmentioning
confidence: 99%
“…Strategy Logic (SL) (Chatterjee, Henzinger, and Piterman 2010;Mogavero et al 2014) was then proposed which, by treating strategies as first-order variables, can express complex game-theoretic concepts. SL has been extended to handle imperfect information and knowledge operators (Berthon et al 2021;Belardinelli et al 2020;Maubert and Murano 2018), but none of these logics can account for quantitative aspects. Recently, SL[F ] (Bouyer et al 2019a) was introduced as a quantitative extension of SL.…”
Section: Related Workmentioning
confidence: 99%
“…However in the imperfect-information setting, we need to know with respect to which observation relation a strategy should be uniform. In (Berthon et al 2021) this is done by parameterizing strategy quantifiers with observation relations. Here we adopt a slightly less general but more intuitive notation, by parameterizing directly with the agent who will use the strategy.…”
Section: Epistemic Sl[f ]mentioning
confidence: 99%
“…Many complex synthesis problems can been expressed in a number of logics for strategic reasoning, notably in Strategy Logic and its variations (Mogavero et al 2014;Berthon et al 2021;Belardinelli et al 2020;Aminof et al 2019b). These allow one to quantify over strategies, and thus can naturally express complex strategic properties, including dominance and maximality.…”
Section: Correctness Of the Construction Of The Automaton A ϕEmentioning
confidence: 99%